Exploring medicine classification and accessibility: a qualitative study - Awangku Khairi Wazien Pengiran Umar; Hui Poh Goh; Zaidah Rizidah Murang; Andi Hermansyah; Inayat Ur Rehman; Khang Wen Goh; Kwan Foong Chee; Long Chiau Ming (Journal of Pharmaceutical Policy and Practice)
Background Brunei Darussalam’s medicine control governance landscape is complex, driven by legislative directives and directed by the Brunei Darussalam Medicines Control Authority (BDMCA). While the medicine dispensing system in Brunei Darussalam, across both governmental and private sectors, is a critical component of the nation’s healthcare, it remains under-researched, leaving gaps in understanding its distinctions, challenges, and opportunities. This study aimed to explore deep into the perspectives of pharmacists regarding the medicine dispensing systems in Brunei Darussalam, medicine accessibility, the classification and regulation of medicines, and the growing role of pharmacists.Methods Using a narrative qualitative approach, we conducted in-depth one-on-one interviews with six pharmacists, delving into their personal experiences with topics such as medicine classification and the broader systems for medication provision. The collected narratives were analysed through a rigorous thematic analysis, following the framework established by Braun & Clarke.Results Five themes emerged from the data: nuances of Brunei Darussalam’s medicine dispensing landscape across both public and private sectors; accessibility and regulatory framework of medicines both in Brunei Darussalam and abroad; prospective implementations to enhance the current system; and the evolving role and expectations of pharmacists in the current healthcare environment. Notably, a significant contribution of this study was the illumination of the differential perspectives between pharmacists operating in governmental versus private contexts.Conclusion This study sheds light on the previously under-explored domain of Brunei Darussalam’s medicine control governance and medicine dispensing system. By drawing from the first-hand experiences of practicing pharmacists, it offers actionable insights that could guide future policy developments, optimise medicine dispensation and regulation, and shape the evolving role of pharmacists in Brunei Darussalam.